Ferrite composite wave-absorbing material and preparation method thereof
By high-temperature ball milling of microcrystalline graphite, manganese carbonate, zinc oxide and iron oxide under an inert atmosphere, ferrite composite wave absorbing material is obtained, which solves the problems of complex preparation process and poor comprehensive performance of composite wave absorbing material in the prior art, and simplified process and performance improvement are achieved.
Patent Information
- Application Number
- CN202411923187.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing composite absorbing materials have complex preparation processes, high costs, and poor comprehensive performance, making it difficult to meet the performance requirements of "thin, light, strong and wide".
Microcrystalline graphite, manganese carbonate, zinc oxide and iron oxide are mixed under an inert atmosphere, and high-temperature ball milling is carried out to produce a ferrite composite wave absorbing material.
The preparation process of composite absorbent materials has been simplified and its comprehensive performance has been significantly improved, including improving absorbent performance, reducing density and optimizing matching thickness and effective absorption band.
Smart Images

Figure CN119706953A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to a ferrite composite wave absorbing material and a preparation method thereof. Background Art
[0002] Although ferrite absorbers have the advantages of high magnetic permeability and wide-band absorption, they also have the disadvantages of high density, poor weather resistance and large coating matching thickness. Due to impedance matching imbalance, absorbers with a single dielectric loss or magnetic loss mechanism are usually difficult to meet the requirements of "thin, light, strong and wide" for good performance absorbers. Carbonaceous materials are typical dielectric loss absorbers. Their high dielectric constant gives them excellent absorption strength, low density and high temperature resistance, but they are limited by a narrow effective absorption band.
[0003] At present, the preparation process of traditional composite absorbing materials is very complicated, costly, and difficult to mass produce. Therefore, it is of great significance to study a ferrite composite absorbing material and its preparation method to achieve a simple preparation process of the composite absorbing material and significantly improve the comprehensive performance of the composite absorbing material. Summary of the invention
[0004] The object of the present invention is to provide a ferrite composite absorbing material and a preparation method thereof, so as to solve the problems of complex preparation process and poor comprehensive performance of the composite absorbing material in the prior art.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing a ferrite composite wave absorbing material, comprising the following steps: in an inert atmosphere, microcrystalline graphite, manganese carbonate, zinc oxide and iron oxide are mixed, and the obtained mixed powder is subjected to high-temperature ball milling to prepare the ferrite composite wave absorbing material.
[0007] In the present invention, the molar ratio of manganese carbonate, zinc oxide and iron oxide is 1-x:x:2, wherein 0<x≤1.
[0008] In the present invention, the molar ratio of manganese carbonate, zinc oxide and iron oxide is 0-0.4:0.6-1:2.
[0009] In the present invention, the molar ratio of the manganese acid, zinc oxide and iron oxide is preferably 0:1:2 or 0.4:0.6:2.
[0010] In the present invention, the microcrystalline graphite is natural microcrystalline graphite (MG) or expanded microcrystalline graphite (EMG).
[0011] In the present invention, the preparation method of expanded microcrystalline graphite (EMG) is as follows: (1) anhydrous aluminum chloride, natural microcrystalline graphite (MG) and N-chlorosuccinimide are mixed, and the obtained mixed powder is subjected to high-temperature ball milling to obtain a ball milling product; (2) the ball milling product is placed in a hydrochloric acid solution for pickling, washing and drying to obtain a graphite intercalation compound, which is recorded as AlCl 3 -MGIC; (3) subjecting the graphite intercalation compound to high temperature treatment to obtain expanded microcrystalline graphite (EMG).
[0012] In the present invention, the mass ratio of anhydrous aluminum chloride, natural microcrystalline graphite and N-chlorosuccinimide is 1:1:0.2 (50g, 50g, 10g); the temperature of the high-temperature ball milling is 200-300°C, preferably 250°C, the speed of the high-temperature ball milling is 30-50rpm, preferably 40rpm, the time of the high-temperature ball milling is 8-12h, preferably 10h, and the ball-to-material ratio of the high-temperature ball milling is 15-25:1, preferably 20:1; the purpose of the pickling is to remove unreacted AlCl 3 The temperature of the high temperature treatment is 800-1000°C, preferably 900°C, and the time of the high temperature treatment is 50-70s, preferably 60s.
[0013] In the present invention, the amount of the microcrystalline graphite added is 5 to 25% based on the mass of the mixed powder.
[0014] In the present invention, the inert atmosphere is an argon atmosphere or a nitrogen atmosphere, preferably an argon atmosphere.
[0015] In the present invention, the temperature of the high-temperature ball mill is 600-800°C, preferably 650-750°C, and more preferably 700°C; the rotation speed of the high-temperature ball mill is 20-60rpm, preferably 30-50rpm, and more preferably 40rpm; the ball-to-material ratio of the high-temperature ball mill is 10-20:1, preferably 12-18:1, and more preferably 15:1; the time of the high-temperature ball mill is 8-12h, preferably 9-11h, and more preferably 10h.
[0016] The present invention also provides a ferrite composite wave absorbing material obtained by the preparation method of the ferrite composite wave absorbing material described above.
[0017] Beneficial effects of the present invention:
[0018] (1) The present invention is based on ZnFe 2 O 4 Adding natural microcrystalline graphite (MG) can improve the ZnFe 2 O 4The absorbing properties of ferrite composite absorbing materials are studied, and the content of MG has a significant effect on the absorbing properties of ferrite composite absorbing materials. As the content of MG increases from 0 to 20%, the minimum reflection loss of the composite absorbing material first increases and then weakens, and reaches a maximum of -62.9dB when m(MG)=10mass%(MG10 / ZFO). At this time, the corresponding matching thickness is 3.9mm, and the effective absorption band covers 5.20~7.10GHz.
[0019] (2) The present invention uses Mn 0.4 Zn 0.6 Fe 2 O 4 The ferrite composite absorber is prepared by adding natural microcrystalline graphite (MG). The minimum reflection loss first increases and then decreases, and reaches the maximum value of -42.1dB when m(MG)=15mass% (MG15 / MZF). At this time, the matching thickness is 1.3mm and the effective absorption bandwidth is 3.94GHz (12.54~16.48GHz). Compared with MG10 / ZFO powder, its matching thickness and effective absorption bandwidth are optimized, but the RL min This is attributed to the enhancement of the magnetic loss capacity of the magnetic component MZF.
[0020] (3) The present invention has a 0.4 Zn 0.6 Fe 2 O 4 The ferrite composite absorber is prepared by adding expanded microcrystalline graphite (EMG). The minimum reflection loss first increases and then decreases, and reaches the maximum value of -56.9dB when m(EMG)=8mass%. At this time, the corresponding effective absorption band covers 11.6~16.3GHz, and the matching thickness is only 1.6mm. Compared with MG10 / ZFO and MG15 / MZF, the matching thickness and effective absorption bandwidth of the sample are optimized, and RL min This is because when the reinforced dielectric component is compounded with the reinforced magnetic component, the impedance matching balance can be achieved at a lower EMG content.
[0021] (4) The absorbing mechanism of ferrite composite absorbers can be attributed to the synergistic effect of enhanced dielectric loss and enhanced magnetic loss. The dielectric loss comes from the dipole polarization, interface polarization and conduction loss provided by the carbonaceous material, and the magnetic loss comes from the eddy current loss and natural resonance provided by the ferrite particles. At the same time, the special three-dimensional porous layered structure of EMG can cause multiple reflections and scattering of the incident electromagnetic wave inside the material, which prolongs the transmission path of the electromagnetic wave, increases the transmission time, and amplifies the effect of dielectric loss and magnetic loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 XRD patterns of EMG, MZF of Comparative Example 1, and ferrite composite absorbing materials of Example 1;
[0023] Figure 2 It is the Raman spectra of EMG and the ferrite composite absorbing material of Example 1;
[0024] Figure 3 FT-IR images of EMG, MZF of Comparative Example 1, and ferrite composite absorbing materials of Example 1;
[0025] Figure 4 is the N of the ferrite composite absorbing material of Example 1 2 Adsorption-desorption isotherms and pore size distribution diagram, where a is N 2 a isotherm diagram of adsorption-desorption, b is the pore size distribution diagram;
[0026] Figure 5 The XPS total spectra of EMG, MZF of Comparative Example 1, and ferrite composite absorbing materials of Example 1, and the high-resolution spectra of the EMG8 / MZF composite absorbing material, wherein a is the XPS total spectrum, and b to f are the elemental high-resolution spectra of C1s, Mn 2p, Zn 2p, Fe 2p, and O 1s in the EMG8 / MZF composite absorbing material, respectively;
[0027] Figure 6 The SEM image and particle size distribution diagram of the ferrite composite absorbing material of Example 1;
[0028] Figure 7 The point composition and element surface distribution diagram of the MZF of comparative example 1 and the MG15 / MZF composite absorbing material of embodiment 3, where a, a 1 is the point component and element surface distribution diagram of MZF, b, b 1 Point composition and element surface distribution diagram of MG / MZF composite absorbing material;
[0029] Figure 8 TEM, HR-TEM images and elemental distribution maps of the EMG8 / MZF composite absorbing material of Example 1, wherein a to c are TEM images, d is a HR-TEM image, and e is an elemental distribution map;
[0030] Fig. 9 1 is a hysteresis loop diagram and a static magnetic parameter distribution diagram of the MZF of Comparative Example 1 and the ferrite composite absorbing material of Example 1, wherein a is a hysteresis loop diagram and b is a static magnetic parameter distribution diagram;
[0031] Fig.10It is a curve diagram of the relationship between the electromagnetic parameters and the frequency of the MZF of Comparative Example 1 and the ferrite composite absorbing material of Example 1, wherein a is ε', b is ε", c is μ', d is μ", e is tanδe, and f is tanδm;
[0032] Fig.11 The three-dimensional R of MG, ZFO of Comparative Example 2 and the ferrite composite absorbing material of Example 2 L Figure, where a is MG, b is ZFO, c is MG5 / ZFO, d is MG10 / ZFO, e is MG15 / ZFO, and f is MG20 / ZFO;
[0033] Fig.12 is a curve diagram showing the relationship between the reflection loss and the frequency of the ferrite composite absorbing material of Example 2 at a specific matching thickness, wherein a is MG5 / ZFO, b is MG10 / ZFO, c is MG15 / ZFO, and d is MG20 / ZFO;
[0034] Fig.13 The three-dimensional R of the ferrite composite absorbing material of Example 3 L Figure and R at a specific thickness L curve, where a, a 1 For MG5 / MZF, b, b 1 MG10 / MZF, c, c 1 For MG15 / MZ, d, d 1 MG20 / MZ;
[0035] Fig.14 The three-dimensional R of the ferrite composite absorbing material of Example 1 L Figure and R at a specific thickness L Curve, where a 1 、a 2 EMG2 / MZF, b 1 、b 2 EMG4 / MZF, c 1 、c 2 For EMG6 / MZF, d 1 d 2 For EMG8 / MZF, e 1 、e 2 For EMG10 / MZF, f 1 、f 2 For EMG15 / MZF, g 1 , g 2 For EMG20 / MZF, h 1 、h 2 For EMG25 / MZF;
[0036] Fig.15The Cole-Cole curve and C of the ferrite composite absorbing material of Example 1 0 -f curve diagram, where a~h are Cole-Cole curve diagrams, a is EMG2 / MZF, b is EMG4 / MZF, c is EMG6 / MZF, d is EMG8 / MZF, e is EMG10 / MZF, f is EMG15 / MZF, g is EMG20 / MZF, h is EMG25 / MZF, and f is C 0 -f curve graph;
[0037] Fig.16 α-f curve graph and Zf curve graph of EMG, MZF of comparative example 1 and ferrite composite absorbing material of embodiment 1, wherein a is the α-f curve graph and b is the Zf curve graph;
[0038] Fig.17 is the R of EMG8 / MZF composite absorbing material at a specific thickness L ,t m , and Z vs. frequency, where a is R L The relationship curve between t and frequency, b is t m The relationship between Z and frequency is shown in the graph, and c is the relationship between Z and frequency.
[0039] Fig.18 Diagram of the potential absorbing mechanism of EMG / MZF composite absorbing material. DETAILED DESCRIPTION
[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0041] The preparation process of expanded microcrystalline graphite (EMG) used in the embodiment of the present invention is as follows: anhydrous aluminum chloride, natural microcrystalline graphite (MG) and N-chlorosuccinimide are mixed, wherein the mass ratio of anhydrous aluminum chloride, natural microcrystalline graphite (MG) and N-chlorosuccinimide is 1:1:0.2 (50g, 50g, 10g), and the obtained mixed powder is subjected to ball milling for 10 hours at a temperature of 250°C, a rotation speed of 40rpm, and a ball-to-material ratio of 20:1 to obtain a ball milling product; the ball milling product is placed in a hydrochloric acid solution (concentration of 0.3mol / L), wherein the mass of the ball milling product and the volume ratio of the hydrochloric acid solution are 100g:1000m, and the pickling is carried out by magnetic stirring for 30min, and then the pickling product is repeatedly washed with deionized water and anhydrous ethanol, and finally dried for 6h to obtain a graphite intercalation compound, recorded as AlCl 3 -MGIC; the graphite intercalation compound is placed in a tube furnace at a temperature of 900°C for 60 seconds to obtain expanded microcrystalline graphite (EMG).
[0042] Example 1
[0043] In an argon atmosphere, manganese carbonate, zinc oxide, iron oxide and EMG are mixed to obtain a mixed powder, in which the molar ratio of manganese carbonate, zinc oxide and iron oxide in the mixed powder is 0.4:0.6:2, and the mass contents of EMG are 2%, 4%, 6%, 8%, 10%, 15%, 20% and 25%, respectively; the mixed powder is ball milled for 10 hours at a temperature of 700°C, a rotation speed of 40 rpm, and a ball-to-material ratio of 15:1 (the grinding balls are stainless steel grinding balls with diameters of 8 mm and 16 mm, respectively, and the mass ratio is 1:2) to obtain ferrite composite absorbing materials, which are respectively recorded as EMG2 / MZF, EMG4 / MZF, EMG6 / MZF, EMG8 / MZF, EMG10 / MZF, EMG15 / MZF, EMG20 / MZF and EMG25 / MZF.
[0044] Example 2
[0045] In an argon atmosphere, zinc oxide, iron oxide and MG are mixed to obtain a mixed powder, in which the molar ratio of zinc oxide to iron oxide is 1:2, and the masses of MG are 5%, 10%, 15% and 20%, respectively. The mixed powder is ball milled for 10 hours at 700°C, 40 rpm, and a ball-to-material ratio of 15:1 (the grinding balls are stainless steel grinding balls with diameters of 8 mm and 16 mm, respectively, and the mass ratio is 1:2) to obtain ferrite composite absorbing materials, which are respectively recorded as MG5 / ZFO, MG10 / ZFO, MG15 / ZFO, and MG20 / ZFO.
[0046] Example 3
[0047] In an argon atmosphere, manganese carbonate, zinc oxide, iron oxide and MG are mixed to obtain a mixed powder, in which the molar ratio of manganese carbonate, zinc oxide and iron oxide in the mixed powder is 0.4:0.6:2, and the mass contents of MG are 5%, 10%, 15% and 20%, respectively. The mixed powder is ball milled for 10 hours at 700°C, 40 rpm, and a ball-to-material ratio of 15:1 (the grinding balls are stainless steel grinding balls with diameters of 8 mm and 16 mm, respectively, and the mass ratio is 1:2) to obtain ferrite composite absorbing materials, which are respectively recorded as MG5 / MZF, MG10 / MZF, MG15 / MZF, and MG20 / MZF.
[0048] Comparative Example 1
[0049] In an argon atmosphere, manganese carbonate, zinc oxide, and iron oxide were mixed in a molar ratio of 0.4:0.6:2, and the obtained mixed powder was ball-milled for 10 hours at a temperature of 700°C, a rotation speed of 40 rpm, and a ball-to-material ratio of 15:1 (the grinding balls were stainless steel grinding balls with diameters of 8 mm and 16 mm, respectively, and a mass ratio of 1:2) to obtain Mn0.4 Zn 0.6 Fe 2 O 4 , denoted as MZF.
[0050] Comparative Example 2
[0051] In an argon atmosphere, zinc oxide and iron oxide were mixed in a molar ratio of 1:2, and the obtained mixed powder was ball milled for 10 hours at a temperature of 700°C, a rotation speed of 40 rpm, and a ball-to-material ratio of 15:1 (the grinding balls were stainless steel grinding balls with diameters of 8 mm and 16 mm, respectively, and a mass ratio of 1:2) to obtain ZnFe 2 O 4 , denoted as ZFO.
[0052] Test method:
[0053] The samples were analyzed for phase and crystal structure using an X-ray diffraction analyzer (XRD, Cu target Kα ray, scanning rate of 5° / min, scanning angle of 10°-80°). The particle size distribution, morphology and element distribution of the samples were observed using a scanning electron microscope (SEM), a transmission electron microscope (TEM) and an X-ray energy dispersive spectrometer (EDS). The Fourier transform infrared spectrometer (FT-IR, wavelength range of 400 cm -1 -4000cm -1 ) to characterize the material composition of the samples; X-ray photoelectron spectroscopy (XPS) to characterize the elemental composition and chemical state of the samples; X-ray fluorescence (XRF) to characterize the composition of MG and its derivatives (Rh target Kα ray, wave number range of 7000cm -1 -350cm -1 ); the specific surface area, pore size distribution and pore volume of the samples were characterized by using a specific surface area and pore size analyzer (BET, test temperature was 77K, degassing temperature and degassing time were 423K and 8h respectively); the graphitization degree and defect degree of the material were characterized by a Raman spectrometer (room temperature, excitation light source was 514nm, wave number range was 200cm -1 -4000cm -1 ); the electromagnetic parameters (ε', ε", μ', μ") of the sample in the frequency range of 2 to 18 GHz were tested by a vector network analyzer (VNA), and then the three-dimensional reflection loss diagram of the sample and the reflection loss value (R L ), C 0 Value, attenuation coefficient (α), impedance matching coefficient (Z) and quarter wavelength (λ / 4) curves.
[0054] Figure 1: The XRD patterns of EMG, MZF of Comparative Example 1 and ferrite composite absorbing materials of Example 1. Figure 1 It can be seen that the ferrite composite absorbers of MZF and Example 1 are both spinel structures. With the addition of EMG, a new characteristic peak appears at 2θ=26.58° in the ferrite composite absorber, corresponding to the (002) crystal plane of graphitized carbon, and the higher the EMG content, the greater the intensity of the diffraction peak. The characteristic peaks of all samples are sharp, well-crystallized, and no impurity peaks are found, indicating that the EMG / MZF composite absorber can be successfully prepared by high-temperature mechanochemical method. At the same time, the strongest peaks of all EMG / MZF powders are the characteristic peaks corresponding to the (311) crystal plane. The characteristic peaks of the composite absorber simultaneously exist in the characteristic peaks of the EMG phase and the MZF phase, indicating that the two have been successfully composited. MZF may have two growth positions during the formation process, one is in the layers and pores of EMG, and the other is on the surface of the EMG sheet. Figure 1 It shows that with the increase of EMG content, the (311) crystal plane corresponding to the strongest characteristic peak of the MZF phase in the ferrite composite absorbing material tends to shift to the right, indicating that the d value decreases. This phenomenon may be due to the fact that under the combined action of high temperature and mechanical force, some C atoms in EMG enter the lattice gap of MZF, causing lattice distortion inside the MZF crystal, thereby increasing the lattice constant.
[0055] Table 1 shows the crystal parameters of the MZF of Comparative Example 1 and the ferrite composite absorber of Example 1. It can be seen from Table 1 that a increases with the increase of EMG content, which may be because the number of C atoms entering the lattice of MZF increases, resulting in an increase in the degree of lattice distortion. In addition, as a increases, the unit cell volume increases. Since the Gibbs free energy is inversely proportional to the particle volume, the Gibbs free energy of the ferrite composite absorber decreases as the EMG content increases. The change in Gibbs free energy may cause differences in the distribution of cations in the material, thereby producing structural differences and affecting the electromagnetic wave absorption capacity of the ferrite composite absorber. η increases with the increase of EMG content, which may be because when the EMG content increases, the "lubricating" effect of graphite is more significant during the ball milling process, thereby increasing the grinding efficiency and reducing the grain size.
[0056] Table 1 Crystal parameters of MZF of Comparative Example 1 and ferrite composite absorbing material of Example 1
[0057]
[0058] Figure 2 Figure 2 is the Raman spectra of EMG and the ferrite composite absorbing material of Example 1. Figure 2It can be seen that compared with EMG, the D band and G band in the ferrite composite absorber are wider, indicating that the degree of defects and lattice deformation in the EMG inside the ferrite composite absorber increase. With the increase of EMG content, the ID / IG value of the ferrite composite absorber increases from 0.10 to 0.21, indicating that with the increase of EMG content, the defect density and disorder of the composite absorber increase. This is because the increase of EMG content will lead to an increase in the carbon (defective component) content. When the unit carbon defect degree is constant, the higher the carbon content, the more defects will be generated. Studies have shown that under the action of an external alternating electromagnetic field, a high defect density is conducive to enhancing the dipole polarization consumption of electromagnetic waves. In addition, more EMG will also provide a more obvious "lubrication effect", thereby improving the ball milling efficiency. The presence of C Raman characteristic peaks was also observed in the spectrum, indicating that the stability of the C basic structure is retained in the prepared composite absorber.
[0059] Figure 3 FT-IR images of EMG, MZF of Comparative Example 1, and ferrite composite absorbing materials of Example 1. Figure 3 It can be seen that compared with EMG, MZF and EMG / MZF composite absorbers have a wave number of about 400-480cm -1 and 480~650cm -1 Two obvious characteristic peaks ν can be observed in the range 1 and ν 2 , corresponding to the [M 3+ -O 2- ] bonds and tetrahedral positions [M 2+ -O 2- ] bond (M=Mn, Zn, Fe). The chemical bonds at the octahedral and tetrahedral positions are formed by the metal ions and O 2- The stretching vibration of the complex, that is, the infrared spectrum of MZF powder is caused by the stretching vibration of O-Fe-O bond, O-Mn-O bond and O-Zn-O bond. At the same time, the existence of tetrahedral and octahedral stretching vibrations also indicates that MZF has a mixed spinel structure. The peak shape of the FT-IR spectrum absorption peak of the EMG / MZF composite absorber is basically consistent with the FT-IR spectrum absorption peak of MZF, but the COC and C=C (CC) bonds in the graphite crystal structure appear. Compared with EMG, the characteristic peaks corresponding to the OH groups in the EMG / MZF composite absorber disappear. In addition, the COC and C=C (CC) bonds are red-shifted, which may be due to the fact that after the composite absorber is formed, the ν 1 and ν 2The bonds may have certain electrostatic interactions with the COC and C=C (CC) bonds in EMG, thereby changing the charge distribution of the functional groups in the composite absorber and the force constant of the chemical bonds, causing the vibration frequency of the functional groups and chemical bonds to change. The FT-IR spectrum of the EMG / MZF composite absorber contains the characteristic absorption peak distribution of the relevant functional groups (chemical bonds) of EMG and MZF, which further indicates that the two have been successfully composited.
[0060] Figure 4 is the N of the ferrite composite absorbing material of Example 1 2 Adsorption-desorption isotherms and pore size distribution diagrams. Figure 4 (a) It can be seen that N of all ferrite composite absorbers 2 The adsorption-desorption curves have similar distribution patterns, both showing type IV curves. 0 <0.04, the absorption / desorption amount showed an upward trend. With the increase of EMG content, the absorption / desorption amount of ferrite composite absorber increased. 0 In the range of 0.4 to 1, an obvious H3 type hysteresis loop appears, indicating that there are both mesoporous and macroporous structures in the sample. This shows that in the process of preparing composite absorbers by high-temperature mechanochemical method, the pore structure in EMG will not be completely destroyed and disappear, and part of the pore structure will still be retained in the composite absorbers. Figure 4 (b) It can be seen that the number of macropores in the ferrite composite absorber decreases while the number of mesopores increases. The reason for the change in pore size may be that during the high-temperature mechanochemical process, the continuous collision between the grinding ball and the EMG causes the pore size of the EMG to decrease. The average pore size, specific surface area and pore volume of the MZF and the ferrite composite absorber in the embodiment were calculated by the BET method. The results are shown in Table 2:
[0061] Table 2 Average pore size, specific surface area and pore volume of ferrite composite absorbers in MZF and Example 1
[0062] sample Average pore size (nm) <![CDATA[Specific surface area (cm 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> ZF 9.76 8.15 0.049 EMG2 / MZF 8.53 4.71 0.021 EMG4 / MZF 8.56 4.60 0.019 EMG6 / MZF 9.16 5.39 0.023 EMG8 / MZF 9.41 6.07 0.026 EMG10 / MZF 9.63 6.75 0.029 EMG15 / MZF 9.48 9.26 0.039 EMG20 / MZF 9.12 10.90 0.040
[0063] As can be seen from Table 2, the specific surface area of the ferrite composite absorbing material increases with the increase of the EMG content. This may be because the edges of the EMG lamellar structure are damaged under the action of mechanical force and peeled into smaller graphite lamellae, thus increasing the specific surface area. The ferrite composite absorbing material has a large specific surface area and a rich pore structure. According to the Maxwell-Garnett theory, the dielectric constant of the porous composite absorbing material can be modified by the pore volume. The multi-level pore structure and appropriate specific surface area are both beneficial to improving the impedance matching characteristics. In addition, the existence of the porous structure can also reduce the density of the composite absorbing material, while providing rich interfaces, defects and active sites. These factors can further introduce multiple polarization relaxations and multiple scatterings, improving the absorbing performance of the material.
[0064] Figure 5 XPS survey spectra of EMG, MZF of Comparative Example 1, the ferrite composite absorbing material of Example 1, and high-resolution spectra of the EMG8 / MZF composite absorbing material. From Figure 5 (a), it can be seen that EMG mainly contains C and O elements; MZF mainly contains Mn, Zn, Fe and O elements; the EMG / MZF composite absorbing materials with different EMG contents mainly contain C, O, Mn, Fe and Zn elements, indicating that EMG and MZF are successfully compounded. Compared with the spectrum of single-phase MZF, the spectrum of the EMG / MZF composite absorbing material shifts to the right. The reason for this phenomenon is the change in electron density caused by the electrical interaction between Zn, Fe, Mn and C atoms due to the introduction of EMG. Specifically, elements with larger electronegativity show a strong attraction to the outer electrons of elements with smaller electronegativity. Given the electronegativity order of each element as Mn(1.55) < Zn(1.65) < Fe(1.83) < C(2.55), Fe and C atoms have a strong attraction to the outer electrons of Mn and Zn atoms and their attraction to their own outer electrons weakens, while the nuclear attraction of Mn and Zn atoms to the outer electrons is stronger, resulting in an increase in the binding energy of Mn and Zn atoms, thus shifting the spectral line of the composite absorbing material to the right. This special interaction is conducive to the charge being bound on the heterogeneous interface, and the resulting charge accumulation can effectively enhance the interfacial polarization effect.
[0065] From Figure 5 (b), it can be seen that the characteristic peaks at binding energies of about 284.8 eV, 285.7 eV and 289.6 eV correspond to C=C / C-C bonds, C-O-C bonds and O-C=O bonds caused by graphite sp 2 hybridized carbon atoms. Among them, the characteristic peak intensity at the C=C / C-C bond is the largest, indicating that EMG still maintains the stability of the basic graphite structure after undergoing swelling or high-temperature mechanical force chemical reactions. Figure 5(c) is the high-resolution spectrum of the Mn element, where Mn 2p exists at binding energies of about 642.6 eV and 654.6 eV. 3 / 2 and Mn 2p 1 / 2 Two characteristic peaks indicate that the Mn element exists in the form of Mn 2+ . Figure 5 (d) is the high-resolution spectrum of Zn element, which also has Zn 2p at the binding energies of about 1022.1eV and 1045.0eV. 3 / 2 and Zn 2p 1 / 2 Two characteristic peaks indicate that Zn exists in the form of Zn 2+ . Figure 5 (e) is the high-resolution spectrum of Fe element, in which there are two forms of band spin-orbit splitting peaks, namely Fe2p 3 / 2 、Fe 2p 1 / 2 As well as the corresponding weak charge transfer satellite peaks, the high-resolution spectrum of the Fe element can be fitted into six different forms of characteristic peaks, corresponding to Fe t 2+ 2p 3 / 2 and Fe t 2+ 2p 1 / 2 The characteristic peaks of Fe at binding energies of about 713.6 eV and 726.9 eV correspond to o 3+ 2p 3 / 2 and Fe o 3+ 2p 1 / 2 The characteristic peaks at the binding energies of about 720.2eV and 734.2eV are satellite peaks of Fe. This indicates that there are Fe located at the tetrahedral sites in the EMG8 / MZF composite absorber. 2+ and octahedral Fe 3+ , indicating that it has a mixed spinel structure. Figure 5 (f) is the high-resolution spectrum of the O element in the EMG8 / MZF composite absorbing material. The characteristic peaks fitted at about 530.5 eV, 531.3 eV and 532.3 eV correspond to the lattice oxygen atoms in the Fe-O bond, Zn-O bond and Mn-O bond in the MZF crystal skeleton, respectively; the characteristic peaks fitted at binding energies of about 531.8 eV and 533.8 eV correspond to the OC=O bond and COC bond, respectively. This shows that the EMG8 / MZF composite absorbing material contains abundant polar functional groups, whose presence is conducive to the generation of dipole polarization loss, thereby enhancing the electromagnetic wave attenuation capability.
[0066] Figure 6 The SEM image and particle size distribution diagram of the ferrite composite absorbing material of Example 1. Figure 6 It can be seen that the ferrite composite absorber is composed of spherical MZF and lamellar EMG. EMG is used to construct a three-dimensional honeycomb carbon matrix conductive network skeleton, in which EMG still retains a relatively obvious layered structure. MZF particles exist between EMG layers and on the surface of EMG. This morphology and composition can optimize impedance matching behavior and act as a "micro capacitor" to store free charges. It can be seen from the particle size distribution diagram that with the increase of EMG content, the average particle size of the ferrite composite absorber decreases from 0.28μm to 0.11μm, and the percentage of small-sized particles increases. This is because EMG can play a certain "lubricating role" in the mechanical force process. The increase in its content will increase the ball milling efficiency and make the interaction between the grinding balls and the reactants more complete, thereby reducing the product particle size. Figure 6 It can also be seen that agglomeration occurs in the ferrite composite absorber, and the degree of agglomeration increases with the increase of EMG content. This is because the surface energy and specific surface area of the product after high-temperature mechanical force treatment increase, resulting in the mutual attraction of MZF particles. In addition, the graphite flakes in EMG may hinder the effect of mechanical force on MZF and affect the dispersion of MZF. The increase in EMG content will provide more sites for the growth / adsorption of MZF particles, resulting in enhanced resistance to mechanical force, and thus an increase in the degree of agglomeration. Adjacent EMG nanosheets and MZF magnetic particles in the ferrite composite absorber can be connected to each other and build a cross-linked conductive network, which increases the transmission speed of particles such as free electrons and ions on the surface between three-dimensional layers, and effectively enhances the interface polarization. At the same time, the unique honeycomb structure of EMG helps to build a perfect conductive network and realize multiple reflections and scattering of electromagnetic waves.
[0067] Figure 7 The point composition and element surface distribution diagram of the MZF of comparative example 1 and the MG15 / MZF composite absorbing material of example 3. Figure 7 a and a 1 It can be concluded that the contents of Mn, Zn, Fe and O are approximately 5.85at%, 8.73at%, 29.63at% and 55.79at%, respectively. Therefore, its chemical composition is Mn 0.4 Zn 0.6 Fe 2 O 4 . Figure 7 b and b 1 It can be concluded that the contents of Mn, Zn, Fe and O in the composite absorbing material are approximately 5.18at%, 8.26at%, 28.97at% and 57.59at%, respectively. Therefore, its chemical composition is Mn 0.4 Zn 0.6 Fe 2 O 4 .
[0068] Figure 8 TEM, HR-TEM and elemental distribution diagrams of the EMG8 / MZF composite absorber of Example 1, wherein a to c are TEM diagrams, d is an HR-TEM diagram, and e is an elemental distribution diagram. It can be seen from the TEM diagram that a large number of spherical MZF particles are randomly distributed inside or on the EMG. It can be seen from the HR-TEM diagram that the diffraction fringes of the EMG / MZF composite absorber are composed of the (002) crystal plane of carbon and the (111), (220), (311), (222), (400), (422), (511) and (440) crystal planes of MZF, which are consistent with the XRD results, further confirming the coexistence of MZF and EMG in the composite absorber. The interplanar spacings of the (002) crystal plane of EMG and the (311) crystal plane of MZF are 0.357nm and 0.260nm, respectively. Compared with single-phase EMG, the lattice spacing of EMG in the composite absorber is reduced, which may be caused by the presence of mechanical force in the high-temperature mechanochemical process, but its lattice spacing is still larger than the standard carbon (002) crystal plane spacing (0.340nm). From the element distribution diagram, it can be seen that the C element is almost uniformly distributed in the entire area, and the distribution of Mn, Zn, Fe and O elements basically overlaps and is located in the C element distribution area, indicating that MZF is distributed in EMG, which basically determines the structure and composition of the EMG / MZF composite absorber. Therefore, during the reaction process, the oxide raw materials react between the EMG layers or on the surface through the action of high temperature and mechanical force to generate MZF particles, forming the EMG / MZF composite absorber.
[0069] Fig. 9 The hysteresis loop diagram and static magnetic parameter distribution diagram of the MZF of comparative example 1 and the ferrite composite absorbing material of embodiment 1, wherein a is the hysteresis loop diagram and b is the static magnetic parameter distribution diagram. It can be seen from the hysteresis loop diagram that the hysteresis loops of all samples are typical "S" type, indicating that they all have soft magnetic properties. s is 72.8emu / g. With the increase of EMG content, the M s Reduce, EMG25 / MZF M s The minimum is only 26.9emu / g. The reason for this trend is that the M of the ferrite composite absorber s and H c They all come from the magnetic MZF particles inside. The increase of non-magnetic component EMG will reduce the content of MZF. The higher the EMG content, the higher the MZF content. s The M of all samples s All in the lower magnetic field range (0~3000O e) increases rapidly, and in the higher magnetic field range (3000~30000O e ) increases slowly and reaches saturation in the entire magnetic field range, indicating that there are both ferromagnetic phase (FM) and antiferromagnetic phase (AFM) in the sample, where the FM phase quickly obtains magnetic response in a lower magnetic field, while the AFM phase exhibits a slower magnetic response in a higher magnetic field. Similarly, the M of the ferrite composite absorber r and H c showed a similar trend, both decreasing with the increase of EMG content. However, this change may be unstable. When the EMG content increased to about 20%, H c and M r This may be because when the external alternating electromagnetic field is applied for demagnetization, the non-magnetic material EMG will generate a certain demagnetization field, which hinders the demagnetization process of the composite absorbing material. When the intensity of the demagnetization process is stronger than the M caused by the reduction of the magnetic component, r and H c When the degree of reduction is r and H c There is an increase in the phenomenon.
[0070] Fig.10 : is a graph showing the relationship between the electromagnetic parameters and the frequency of the MZF of Comparative Example 1 and the ferrite composite absorbing material of Example 1, wherein a is ε', b is ε", c is μ', d is μ", e is tanδe, and f is tanδm; Fig.10It can be seen from a and b that the ε' values of all samples decrease with increasing frequency (frequency dispersion behavior), which is caused by the inability of the dipoles inside the material to quickly reorient in response to changes in the frequency of the applied electromagnetic field. The ε' and ε" of MZF fluctuate around 4.0 and 0, respectively, which indicates that the single-phase MZF basically has no electrical loss capacity; when the EMG content increases to 25%, the ε' and ε" of the ferrite composite absorber increase to 22.0-45.0 and 12.0-40.0, respectively, indicating that the composite of EMG and MZF can significantly enhance its electrical storage and electrical loss capabilities, and the greater the amount of EMG added, the more obvious the corresponding ε' and ε" increase. It is generally believed that the dielectric loss of the material mainly comes from conduction loss and polarization loss. The higher the conductivity of the material, the better its dielectric properties. With the increase of EMG content, the more complete the conductive network in the composite absorber is, which promotes the directional jumping and migration of electrons, making the conductivity significantly The dielectric loss and conduction loss are significantly enhanced, thereby enhancing the dielectric loss and conduction loss in the process of electromagnetic wave absorption. In addition, the ε' value of the ferrite composite absorber with high EMG content decreases more significantly in the entire frequency range. This may be because the increase in EMG content may provide more polarized molecules and free electrons, greatly improving the composite absorber's ability to respond to electromagnetic waves at high frequencies. Multiple dielectric resonance peaks can be observed in the ε" curve, which can be attributed to the existence of polarization. The polarization phenomenon inside the material may have the following sources: First, when the dipole inside the material cannot respond quickly to the frequency change of the external alternating electromagnetic field, it will induce dipole polarization; second, a large number of heterogeneous interfaces (such as SiO 2 / C、Al 2 O 3 / C and Fe 2 O 3 / C, etc.), which can act as a polarization center to produce interface polarization under the action of an external alternating electromagnetic field; finally, the product introduces a large number of structural defects under the action of mechanical force, and these defects will cause polarization effects under the action of an external alternating electromagnetic field; the existence of the above forms of polarization is conducive to improving the dielectric loss capacity of composite absorbing materials. In addition, due to the Maxwell-Wagner effect, a large amount of bound charges will accumulate at the heterogeneous interface inside the material under the action of high-frequency electromagnetic fields. When the charges accumulate to a certain extent, they will be released to form microcurrents, thereby enhancing conduction losses. It can be seen that increasing the EMG content can significantly improve the dielectric loss capacity of composite absorbing materials. However, too much EMG may lead to agglomeration and accumulation, reduce the number of effective interfaces, hinder the movement of carriers on the heterogeneous interface, and weaken the interface polarization effect. From FT-IR and XPS analysis, it can be seen that there are a large number of oxygen-containing functional groups (such as COC and OC=O, etc.) on the EMG surface of the composite absorbing material. The C and O atoms in these functional groups will show different attraction and binding abilities to free electrons, produce electron pair differences inside the material, and induce dipole polarization under the action of an external alternating electromagnetic field. However, the higher the ε' and ε" values are, the better. Too high ε' and ε" values may lead to an imbalance in impedance matching and have a negative impact on the absorbing performance of the material.
[0071] Fig.10 As can be seen from c and d, μ' and μ" of all samples decrease in the range of 2 to 6 GHz and tend to be stable in the range of 6 to 18 GHz. The curves show similar dispersion phenomena in both high-frequency and low-frequency regions, indicating that natural resonance and exchange resonance may exist in the material. For spinel ferrite, exchange resonance only occurs in the THz frequency range, so the magnetic loss in this sample comes from natural resonance. With the increase of EMG content, μ' and μ" of ferrite composite absorbers both decrease, indicating that the magnetic loss capacity is weakened. This is because the increase of EMG content will lead to a decrease in the content of magnetic components in the ferrite composite absorbers, thereby reducing the complex magnetic permeability, which is consistent with the conclusion drawn from the static magnetic properties analysis.
[0072] Fig.10It can be seen from e and f that as the EMG content increases, the value of tanδe of the ferrite composite absorbing material increases accordingly, reflecting the enhancement of the dielectric loss ability of the ferrite composite absorbing material. MZF has tanδe < tanδm throughout the frequency range, indicating that magnetic loss is its main electromagnetic wave loss mechanism. For the ferrite composite absorbing material, when the EMG content is 2%, 4%, 6%, 8%, and 10%, tanδe < tanδm in the low-frequency range (about 2 - 8 GHz) for the samples, indicating that the loss mechanism is mainly magnetic loss at this time; in the high-frequency range (about 8 - 18 GHz), tanδe > tanδm, indicating that the loss mechanism is mainly dielectric loss at this time. When the EMG content is 15%, 20%, and 25%, tanδe > tanδm throughout the frequency range, indicating that the loss mechanism is mainly dielectric loss at this time. This shows that the content of EMG has a great influence on the type of the main loss mechanism of the ferrite composite absorbing material. As the EMG content increases, the main loss mechanism of the ferrite composite absorbing material gradually transitions from magnetic loss to dielectric loss. It can also be seen from the figure that as the EMG content increases, the values of tanδe and tanδm show an increasing and decreasing trend respectively, indicating that adding EMG to the ferrite absorbing material weakens the magnetic loss while enhancing the dielectric loss ability, which is consistent with the relevant analysis of the electromagnetic parameters.
[0073] Fig.11 Three-dimensional R of MG, ZFO of Comparative Example 2, and the ferrite composite absorbing material of Example 2 L Figure, where a is MG, b is ZFO, c is MG5 / ZFO, d is MG10 / ZFO, e is MG15 / ZFO, and f is MG20 / ZFO. From Fig.11 It can be seen that the RL of the single-phase ZFO powder at a matching thickness of 5.0 mm is min -10.66 dB. As the MG content increases, the RL of the composite absorbing material min first increases and then decreases, reaching the maximum at m(MG) = 10 mass%, which is -62.90 dB. The corresponding matching thickness at this time is 3.9 mm, and the effective absorption frequency band covers 5.20 - 7.10 GHz. In addition to the enhanced absorbing ability, the matching thickness corresponding to obtaining RL of the composite absorbing material also decreases. MG20 / ZFO can obtain RL min when the matching thickness is only 1.7 mm. min Therefore, the absorbing performance meeting specific requirements can be obtained by changing the MG content in the composite absorbing material.
[0074] Fig.12: is a graph showing the relationship between reflection loss and frequency of the ferrite composite absorber of Example 2 at a specific matching thickness, wherein a is MG5 / ZFO, b is MG10 / ZFO, c is MG15 / ZFO, and d is MG20 / ZFO. Fig.12 It can be seen that with the increase of matching thickness, the RL of the composite absorber min All of them move toward the low frequency direction, indicating that they have better absorbing performance in the low frequency band. Therefore, different absorbing performance can be obtained by changing the matching thickness of the composite absorbing material.
[0075] Fig.13 The three-dimensional RL diagram of the ferrite composite absorbing material of Example 3 and the RL curve at a specific thickness. Fig.13 It can be seen that the MG content has a significant effect on the microwave absorption performance of the composite material. When m(MG)=5mass%, the RL min The RL of the sample increases from -17.2dB to -17.2dB, and the corresponding matching thickness is only 1.6mm. The effective absorption band covers 10.56 to 13.08GHz. min n reaches -42.1dB (electromagnetic wave absorption rate is 99.994%), the matching thickness is 1.3mm, and the effective absorption bandwidth is 3.94GHz. When m(MG) = 20mass%, the sample obtains RL min The corresponding matching thickness increases to 3.4 mm, which can be attributed to the impedance matching imbalance caused by excessive MG content. min All of them move toward the low frequency direction, indicating that they have better microwave absorption performance in the low frequency band. In summary, MG can significantly improve the microwave absorption performance of MZF. At the same time, the microwave absorption performance of the composite material can be adjusted by changing the MG content and matching thickness.
[0076] Fig.14 The three-dimensional R of the ferrite composite absorbing material of Example 1 L Figure and R at a specific thickness L Curve, where a 1 、a 2 EMG2 / MZF, b 1 、b 2 EMG4 / MZF, c 1 、c 2 For EMG6 / MZF, d 1 d 2 For EMG8 / MZF, e 1 、e 2 For EMG10 / MZF, f 1 、f 2 For EMG15 / MZF, g1 , g 2 For EMG20 / MZF, h 1 、h 2 For EMG25 / MZF. Fig.14 It can be seen that EMG can significantly improve the microwave absorption performance of MZF powder, and the RL of the sample increases with the increase of EMG content. min When m(EMG)=2mass%, the sample has two strong absorption peaks when the matching thickness is 6.9mm and 9.6mm, and the corresponding RL min They are -41.2dB (corresponding to 99.9924% electromagnetic wave absorption rate) and -43.8dB (corresponding to 99.9958% electromagnetic wave absorption rate). min When m(EMG) = 8mass%, the RL of the composite absorbing material min The maximum value is -56.9dB (corresponding to 99.9998% electromagnetic wave absorption rate), and the effective absorption band covers 11.6~16.3GHz (almost covering the entire Ku band). At this time, the matching thickness is only 1.6mm. Continuing to increase the content of EMG, the RL of the sample min When m(EMG) = 25mass%, the corresponding RL min The final value is -8.2 dB (corresponding to 84.8644% electromagnetic wave absorption rate). Although the RL of the composite absorber increases with the increase of EMG when m(EMG)>8mass%. min It shows a downward trend, but its RL min The corresponding matching thickness is getting thinner. In addition, with the increase of matching thickness, the RL of all samples min All of them move toward the low frequency direction, indicating that their absorbing performance is better in the low frequency range.
[0077] Fig.15 The Cole-Cole curve and C of the ferrite composite absorbing material of Example 1 0 -f curve diagram, where a~h are Cole-Cole curve diagrams, a is EMG2 / MZF, b is EMG4 / MZF, c is EMG6 / MZF, d is EMG8 / MZF, e is EMG10 / MZF, f is EMG15 / MZF, g is EMG20 / MZF, h is EMG25 / MZF, and f is C 0-f curve. From a to h, it can be concluded that with the increase of EMG content, the radius and number of Cole semicircles in the curve increase, indicating that increasing the EMG content can enhance the dielectric loss capacity of ferrite composite absorbers. The Cole curves of all samples are composed of twisted semicircles and "straight tails", indicating that their dielectric losses are composed of multiple polarization relaxation and conduction losses. Among them, the multiple polarization relaxation process can be attributed to the dipole polarization caused by the abundant functional groups and defects in the composite absorber, and the interface polarization constructed by multiple heterogeneous interfaces. The conduction loss is attributed to the introduction of conductive components (such as C and Al 2 O 3 , Fe 2 O 3 , MgO and CaO and other trace oxides), by enhancing the conductivity of the ferrite composite absorber and thus enhancing its conduction loss. At the same time, the distortion of the Cole semicircle can be attributed to the defects in the particles and the lattice distortion. With the increase of EMG content, the number and radius of the Cole semicircles first increase and then decrease, indicating that the dielectric loss capacity of the ferrite composite absorber first increases and then weakens, and reaches the maximum value when m(EMG)=8mass%. The reason for the enhancement of the number and radius of Cole semicircles can be attributed to the existence of a large number of inhomogeneous interfaces, which hinder the movement of charges and lead to uneven distribution of electrons on the interface. In addition, the cation defects in the composite absorber are also conducive to the generation of dipole polarization. With the increase of EMG content, it can be observed that the ordinate value of the center of the Cole semicircle in the curve increases, indicating that the conductivity of the sample is enhanced. As can be seen from f, they show similar trends in the entire frequency range. With the increase of frequency, the C of all samples 0 They all gradually decrease in the range of 2 to 10 GHz and tend to be stable in the range of 10 to 18 GHz, indicating that the magnetic loss of ferrite composite absorbers is composed of natural resonance and eddy current loss, among which the natural resonance comes from the magnetocrystalline anisotropy of ferrite particles.
[0078] Fig.16 The α-f curve and Zf curve of the ferrite composite absorbing material of EMG, MZF of comparative example 1 and embodiment 1, where a is the α-f curve and b is the Zf curve. It can be seen from the α-f curve that the α of all samples increases with the increase of frequency, indicating that they have stronger attenuation capabilities in the high frequency band. Single-phase EMG has the largest α among all samples, and its value is distributed between 600 and 1600; single-phase MZF has a lower value of ~. The α of the composite absorbing material increases with the increase of EMG content, indicating that EMG can significantly enhance the attenuation capacity of MZF, and the higher the EMG content, the more obvious the enhancement effect. As mentioned above for R LThe analysis found that although the α values of EMG and EMG25 / MZF powders are greater than that of EMG8 / MZF powders, their absorbing performance is weaker than that of EMG8 / MZF powders, which may be related to their impedance matching characteristics. From the Zf curve, it can be seen that the Z value of single-phase MZF is larger. With the increase of EMG content in the composite absorbing material, the Z value gradually decreases and approaches the Z value of single-phase EMG. The reason for this trend is that the increase in EMG content leads to an increase in the conductivity of the composite absorbing material. Among them, the Z value of EMG8 / MZF powder is between 0.9 and 1.1 in 11-14GHz, while the Z values of other samples are far away from this range, indicating that the impedance matching characteristics of EMG8 / MZF powder are better. The larger conductivity of single-phase EMG leads to its poor impedance matching characteristics. After compounding with MZF, a large number of heterogeneous interfaces are introduced between the two, thereby reducing the conductivity, making the two reach electromagnetic balance, and optimizing the impedance matching characteristics. In addition, the SiO contained in EMG 2 、MnO 2 and TiO 2 The impedance matching characteristics between the absorbing material and the free space can also be improved, so the impedance matching characteristics of the composite absorbing material are better than those of the single-phase EMG and MZF. The absorbing performance of the material is determined by its α and Z. Although the composite absorbing material with a higher EMG content has a stronger α, its impedance matching characteristics are deteriorated. Therefore, the appropriate EMG content is a necessary condition for obtaining a composite absorbing material with excellent absorbing performance.
[0079] Fig.17 is the R of EMG8 / MZF composite absorbing material at a specific thickness L ,t m , and Z vs. frequency, where a is R L The relationship curve between t and frequency, b is t m The relationship between Z and frequency is shown in Fig. 1, and c is the relationship between Z and frequency. From a, we can see that as the thickness of the sample increases, RL min The frequency of t moves to the low frequency region, which can be explained by the quarter-wavelength theory, which means that there is a phase cancellation effect in the sample. The black curve in b is the t calculated by the quarter-wavelength theory. m The red dots are the actual matching thickness. It can be seen that the matching thickness obtained by experiment is consistent with the theoretical calculation of t m The agreement is good (|Δ| < 0.1), and these thicknesses are also consistent with aRL min The thickness of the sample at different matching thicknesses is consistent. L The positions correspond to those when Z = 1, and the closer Z is to 1, the higher the R LThe stronger the absorption, the better the absorption performance of the composite absorber material. In other words, the quarter wavelength determines the thickness of the absorption layer, while the impedance matching determines its absorption strength.
[0080] Absorption mechanism of EMG / MZF composite absorber: Since EMG / MZF composite absorber has good compatibility between dielectric loss and magnetic loss, it has excellent electromagnetic wave attenuation ability. Its potential absorption mechanism is as follows: Fig.18 As shown. When the incident electromagnetic wave is emitted from free space to the surface of the absorber and contacts it, part of the incident electromagnetic wave will be directly reflected back into the free space; another part will enter the interior and interact with the absorber. Under the action of various loss mechanisms, the electromagnetic energy will be converted into other forms of energy and attenuated or dissipated; in addition, there may be a very small amount of residual electromagnetic waves returning to the free space after penetrating the absorption layer. The mechanism of attenuation or dissipation of electromagnetic waves entering the absorber may include: (1) Due to the collision between the grinding balls and the materials during the preparation process, a large number of defects will be introduced into MZF and EMG. At the same time, there are a large number of oxygen-containing functional groups in EMG, which will show different attraction and binding abilities for electrons. Under the action of an external alternating electromagnetic field, these defects and functional groups can act as polarization and scattering centers to induce dipole polarization. (2) The composite absorber has abundant heterogeneous interfaces (such as MZF / SiO 2 、MZF / Al 2 O 3 、MZF / Fe 2 O 3 and Fe 2 O 3 / C, etc.), the existence of these heterogeneous interfaces will cause the local charge in the contact area to change, thereby inducing interface polarization. (3) The composite absorber has a certain specific surface area. At the same time, the combination of honeycomb three-dimensional EMG and one-dimensional MZF and trace oxide particles in EMG can construct a relatively complete three-dimensional conductive network, which is conducive to the transition of free electrons, thereby enhancing the conduction loss and effectively converting electromagnetic energy into heat energy. (4) The magnetic MZF particles give the composite absorber a strong magnetic loss capacity, which mainly comes from natural resonance and eddy current loss. (5) There are rich multi-layer pore structures and interconnected conductive networks inside the composite absorber, which not only provides the possibility for multiple reflections and scattering of the incident electromagnetic wave inside the material, but also prolongs the propagation time and path of the electromagnetic wave, amplifies the role of dielectric loss and magnetic loss, and improves the attenuation efficiency of the electromagnetic wave. Under the joint action of the above mechanisms, the composite absorber achieves a good coupling effect of dielectric loss and magnetic loss, while satisfying a strong attenuation coefficient and good electromagnetic impedance matching characteristics, showing excellent absorbing performance.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a ferrite composite absorbing material, characterized in that: The method comprises the following steps: in an inert atmosphere, microcrystalline graphite, manganese carbonate, zinc oxide and iron oxide are mixed, and the obtained mixed powder is subjected to high-temperature ball milling to obtain a ferrite composite wave absorbing material.
2. The method for preparing the ferrite composite absorbing material according to claim 1, characterized in that: The molar ratio of the manganese carbonate, zinc oxide and iron oxide is 1-x:x:2, wherein 0<x≤1.
3. The method for preparing the ferrite composite absorbing material according to claim 2, characterized in that: The molar ratio of the manganese carbonate, zinc oxide and iron oxide is 0-0.4:0.6-1:
2.
4. The method for preparing a ferrite composite absorbing material according to any one of claims 1 to 3, characterized in that: The microcrystalline graphite is natural microcrystalline graphite or expanded microcrystalline graphite.
5. The method for preparing the ferrite composite absorbing material according to claim 4, characterized in that: The added amount of the microcrystalline graphite is 5-25% based on the mass of the mixed powder.
6. The method for preparing the ferrite composite absorbing material according to claim 3 or 5, characterized in that: The inert atmosphere is an argon atmosphere or a nitrogen atmosphere.
7. The method for preparing the ferrite composite absorbing material according to claim 6, characterized in that: The temperature of the high-temperature ball mill is 600-800° C., the rotation speed of the high-temperature ball mill is 20-60 rpm, the ball-to-material ratio of the high-temperature ball mill is 10-20:1, and the time of the high-temperature ball mill is 8-12 hours.
8. The ferrite composite wave absorbing material obtained by the preparation method of the ferrite composite wave absorbing material according to any one of claims 1 to 7.
Citation Information
Patent Citations
Zinc ferrite-graphite composite powder as well as preparation method and application thereof
CN118164541A